Challenges in horizontal integration of eye care services into the pre-existing rural primary care structure: an operations research perspective from Nigeria - Ezisi, Chinyere Nkemdilim; Eze, Boniface Ikenna; Okoye, Obiekwe; Chuka-Okosa, Chimdi Memnofu; Shiweobi, Jude Obinna (Family Medicine & Primary Care Review, 2017)
Background . The provision of population-wide, accessible, affordable, acceptable and evenly distributed qualitative eye care services remains a recurrent challenge to eye care organizations worldwide. Objectives . To report the challenges encountered in setting up eye care service in a pre-existing primary health care facility in rural Nigeria and also audit the common causes of eye disorders in rural setting southeast of Nigeria. Material and methods . The study was an operations research study conducted at Akpuoga-Nike between February and April 2011. Demographic and ophthalmic clinical data were collected. Health system-, community- and patient-determined challenges were catalogued and analyzed using Epi Info Statistical software for Windows, version 6. Univariate analysis was performed for data distribution testing. Analytical statistics were performed, with p < 0.05 considered statistically significant. Results . A total of 481 (males, 144 (29.9%); females, 377(70.1%)) patients aged 42.3 ± 20.2 SD years (range 4–80 years) were seen. The leading eye disorders were refractive error – 28.9%, and cataract – 16.4%. The operations challenges encountered included difficulties with community sensitization/advocacies, inadequate infrastructure and mobile equipment, as well as lack of eye care manpower, consumables and funding deficits. Conclusions . Health system-related issues were the main challenges encountered. Recruitment of an adequate number of rural eye care workforce, provision of needed material resources, adequate funding and engendering community participation in rural eye care delivery through grass roots advocacy and health service public education would overcome the challenges.